2011
DOI: 10.1152/jn.00419.2011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of persistent inward currents, accommodation, and adaptation on motor unit behavior: a simulation study

Abstract: Revill AL, Fuglevand AJ. Effects of persistent inward currents, accommodation, and adaptation on motor unit behavior: a simulation study. J Neurophysiol 106: 1467-1479. First published June 22, 2011 doi:10.1152/jn.00419.2011.-Motor neurons are often assumed to generate spikes in proportion to the excitatory synaptic input received. There are, however, many intrinsic properties of motor neurons that might affect this relationship, such as persistent inward currents (PICs), spike-threshold accommodation, or spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 109 publications
(140 reference statements)
3
45
0
Order By: Relevance
“…Figure 4 compares ⌬F values for triangular contractions with three different rise times (short: 2.5 s, standard: 5 s, long: 10 s) as well as ramp and hold contractions with ramp rise times of 5 s, but different duration hold phases (5 and 10 s). In agreement with Revill and Fuglevand (2011), contraction duration had no significant effect on ⌬F values in the absence of any spike frequency adaptation (Fig. 4A, one-way ANOVA, F ϭ 1.068, nonsignificant).…”
Section: Interaction Of Contraction Speed and Duration With The Effecsupporting
confidence: 87%
See 4 more Smart Citations
“…Figure 4 compares ⌬F values for triangular contractions with three different rise times (short: 2.5 s, standard: 5 s, long: 10 s) as well as ramp and hold contractions with ramp rise times of 5 s, but different duration hold phases (5 and 10 s). In agreement with Revill and Fuglevand (2011), contraction duration had no significant effect on ⌬F values in the absence of any spike frequency adaptation (Fig. 4A, one-way ANOVA, F ϭ 1.068, nonsignificant).…”
Section: Interaction Of Contraction Speed and Duration With The Effecsupporting
confidence: 87%
“…The simulation results of Revill and Fuglevand (2011) suggested that the drop in firing rate produced by adaptation mechanisms should increase with contraction duration, and that the resulting increase in firing rate modulation in the lower threshold reporter unit between recruitment and de-recruitment of the higher threshold test unit would lead to higher ⌬F values. Figure 4 compares ⌬F values for triangular contractions with three different rise times (short: 2.5 s, standard: 5 s, long: 10 s) as well as ramp and hold contractions with ramp rise times of 5 s, but different duration hold phases (5 and 10 s).…”
Section: Interaction Of Contraction Speed and Duration With The Effecmentioning
confidence: 99%
See 3 more Smart Citations